1999
DOI: 10.1038/sj.ijo.0800967
|View full text |Cite
|
Sign up to set email alerts
|

Dietary underreporting is prevalent in middleaged British women and is not related to adiposity (percentage body fat)

Abstract: A low reported EI and greater BMI may help identify energy underreporters. However, whilst underreporters may more frequently be 'bigger' (by BMI), they are not necessarily fatter (using direct measures of body fat). As underreporting was present among all tertiles of BMI and adiposity, these results emphasise the importance of following past recommendations to identify and exclude energy underreporters in nutritional studies. Where underreporters have not been excluded, reported nutrition-disease relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 23 publications
4
22
1
Order By: Relevance
“…Actual differences in activity and intake patterns for families with obesigenic vs non-obesigenic tendencies may be even greater than those identified in this study as research shows that people tend to under-report dietary intake 40 and over-report physical activity 25 and suggests that this pattern may be more pronounced among overweight and obese persons. 41 -43 This bias was also present in this study as subjects who were heavier reported lower intakes than would be expected based on their weight (as shown by a negative sample mean value for energy intake residualized for body weight in Table 1).…”
Section: Discussioncontrasting
confidence: 43%
“…Actual differences in activity and intake patterns for families with obesigenic vs non-obesigenic tendencies may be even greater than those identified in this study as research shows that people tend to under-report dietary intake 40 and over-report physical activity 25 and suggests that this pattern may be more pronounced among overweight and obese persons. 41 -43 This bias was also present in this study as subjects who were heavier reported lower intakes than would be expected based on their weight (as shown by a negative sample mean value for energy intake residualized for body weight in Table 1).…”
Section: Discussioncontrasting
confidence: 43%
“…The ratio of reported energy intake (EI) to BMR was used to estimate the prevalence of under-and overreporting. A cut-off point of EI , 1.35 £ BMR, estimated based on sedentary subjects in calorimeters, was used to identify implausibly low energy intakes, as in other studies 10,22,24,25 . As elsewhere, overreporting was defined as EI .…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…Studies involving urinary nitrogen as a biomarker for total protein intake have also been consistent with this conclusion 2,3 . However, obesity-related underreporting may not be a universal phenomenon, and there is evidence that fatness per se may be less predictive of underreporting than body size 4,5 . This paper briefly reviews a number of issues relevant to interpreting dietary data in studies involving obesity.…”
mentioning
confidence: 99%